The role of microRNA in cisplatin resistance or sensitivity. (1st September 2020) - Wang, Shanshan; Li, Ming-Yue; Liu, Yi; Vlantis, Alexander C; Chan, Jason YK; Xue, Lingbin; Hu, Bao-Guang; Yang, Shucai; Chen, Mo-Xian; Zhou, Shaoming; Guo, Wei; Zeng, Xianhai; et al.
ABSTRACT: Introduction: Cisplatin is a chemotherapy drug that has been used to treat a number of cancers for decades, and is still one of the most commonly used anti-cancer agents. However, some patients do not respond to cisplatin while other patients who were originally sensitive to cisplatin eventually develop chemoresistance, leading to treatment failure or/and tumor recurrence. Areas Covered: Different mechanisms contribute to cisplatin resistance or sensitivity, involving multiple pathways or/and processes such as DNA repair, DNA damage response, drug transport, and apoptosis. Among the various mechanisms, it appears that microRNAs play an important role in determining the resistance or sensitivity. In this article, we analyzed and summarized recent findings in this area, with the aim that these data can aid further research and understanding, leading to the eventual reduction of cisplatin resistance. Expert Commentary: microRNAs can positively or negatively regulate cisplatin resistance by acting on molecules or/and pathways related to apoptosis, autophagy, hypoxia, cancer stem cells, NF-κB, and Notch1. It appears that the modulation of relevant microRNAs can effectively re-sensitize cancer cells to cisplatin regimen in certain types of cancers including breast, colorectal, gastric, liver, lung, ovarian, prostate, testicular, and thyroid cancers.